Intangible Investment and Technical Efficiency: The Case of Software-Intensive Manufacturing Firms in Turkey - Derya Findik; Aysit Tansel (Institute for the Study of Labor (IZA), 2015)
This chapter analyzes the effect of intangible investment on firm efficiency with an emphasis on its software component. Stochastic production frontier approach is used to simultaneously estimate the production function and the determinants of technical efficiency in the software intensive manufacturing firms in Turkey for the period 2003-2007. Firms are classified based on the technology group. High technology and low technology firms are estimated separately in order to reveal differentials in their firm efficiency. The results show that the effect of software investment on firm efficiency is larger in high technology firms which operate in areas such as chemicals, electricity, and machinery as compared to that of the low technology firms which operate in areas such as textiles, food, paper, and unclassified manufacturing. Further, among the high technology firms, the effect of the software investment is smaller than the effect of research and development personnel expenditure. This result shows that the presence of R&D personnel is more important than the software investment for software intensive manufacturing firms in Turkey.
Keywords: L21; L22; L23; L25; 330; intangible assets; software investment; efficiency; software intensive firms; stochastic frontier analysis; production function; firms; Turkey